CYP2C19*17 May Increase the Risk of Death Among Patients with an Acute Coronary Syndrome and Non-Valvular Atrial Fibrillation Who Receive Clopidogrel and Rivaroxaban - Sychev DA; Baturina OA; Mirzaev KB; Rytkin E; Ivashchenko DV; Andreev DA; Ryzhikova KA; Grishina EA; Bochkov PO; Shevchenko RV (Dove Medical Press, 2020)
DA Sychev,1 OA Baturina,2 KB Mirzaev,1 E Rytkin,1 DV Ivashchenko,1 DA Andreev,2 KA Ryzhikova,1 EA Grishina,1 PO Bochkov,1 RV Shevchenko1 1Russian Medical Academy of Continuous Professional Education, Ministry of Health of the Russian Federation, Moscow, Russian Federation; 2Sechenov University, Moscow, Russian FederationCorrespondence: E RytkinRussian Medical Academy of Continuous Professional Education, Ministry of Health of the Russian Federation, Moscow, Russian FederationEmail erytkin@gmail.comIntroduction: The aim of this study is to assess the influence of gene CYP2C19, CYP3A4, CYP3A5 and ABCB1 polymorphisms on clopidogrel antiplatelet activity, rivaroxaban concentration equilibrium, and clinical outcomes among patients with acute coronary syndrome and non-valvular atrial fibrillation.Methods: In the multicenter prospective registry study of the efficacy and safety of a combined antithrombotic therapy 103 patients with non-valvular atrial fibrillation both undergoing or not a percutaneous coronary intervention were enrolled. The trial assessed the primary outcomes (major bleeding, in-hospital death, cardiovascular death, stroke ransient ischaemic attack, death/renal insufficiency) and secondary outcomes (platelet reactivity units (PRU), rivaroxaban concentration).Results: For none of the clinical outcomes when combined with other covariates, the carriership of polymorphisms CYP3A5*3 rs776746, CYP2C19*2 rs4244285;*17 rs12248560, ABCB1 3435 C>T, ABCB1 rs4148738 was significant. None of the markers under study (CYP3A5*3 rs776746, CYP2C19*2 rs4244285, *17 rs12248560, ABCB1 3435 C>T, ABCB1 rs4148738) has proven to affect rivaroxaban equilibrium concentration in blood plasma among patients with atrial fibrillation and acute coronary syndrome.Conclusion: In situations of double or triple antithrombotic rivaroxaban and clopidogrel therapy among patients with atrial fibrillation and acute coronary syndrome, the genetic factors associated with bleeding complications risk (CYP2C19*17) may prove to be clinically relevant.Keywords: rivaroxaban, clopidogrel, polymorphism, atrial fibrillation, acute coronary syndrome